A DFT‐based study of the hydrogen‐bonding interactions between epicatechin and methanol/water. Issue 1 (26th December 2022) - Liu, Qifan; Xiao, Kelaiti; Abulimiti, Bumaliya; Xiang, Mei; Wang, Danqi; An, Han; Zheng, Jingyan
Abstract: Tea polyphenols are essential components that give tea its medicinal properties. Methanol and water are frequently used as solvents in the extraction of polyphenols. Hydrogen‐bonding interactions are significant in the extraction reaction. Density functional theory (DFT) techniques were used to conduct a theoretical investigation on the hydrogen‐bonding interactions between methanol or water and epicatechin, an abundant polyphenol found in tea. After first analyzing the epicatechin monomer's molecular geometry and charge characteristics, nine stable epicatechin (EC) H2 O/CH2 OH complex geometries were discovered. The presence of hydrogen bonding in these improved structures has been proven. The calculated hydrogen bond structures are very stable, among which the hydrogen bond bonded with a hydroxyl group has higher stability. The nine complex structures' hydrogen bonds were thought to represent closed‐shell‐type interactions. The interaction energy with 30O‐31H on the epicatechin benzene ring is the strongest in the hydrogen bond structure. While the other hydrogen bonds were weak in strength and mostly had an electrostatic nature, the hydrogen bonds between the oxygen atoms in H2 O or CH2 OH and the hydrogen atoms of the hydroxyl groups in epicatechin were of moderate strength and had a covalent character. Comparing the changes in the hydrogen bond structure vibration peak, the main change in concentration peak is the hydrogen bond vibration peak in the complex. Improved the study on the hydrogen bond properties of CH2 OH and H2 O of EC. Abstract : Tea polyphenols are essential components that give tea its medicinal properties. Methanol and water are frequently used as solvents in the extraction of polyphenols. Hydrogen‐bonding interactions are significant in the extraction reaction. Density functional theory (DFT) techniques were used to conduct a theoretical investigation on the hydrogen‐bonding interactions between methanol or water and epicatechin, an abundant polyphenol found in tea.